The Influence of UTAUT2 Variables on Online Health Information Seeking Behavior for Symptoms Checking - Yanuar, Norman (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2025)
This study explores the influence of the UTAUT2 variables on Online Health Information Seeking Behavior for symptoms checking. This study used PLS-SEM analysis on 156 respondents who had searched for health information online for symptoms checking. The results show that Habit and Effort Expectancy most influence health information seeking behavior, followed by Performance Expectancy and Social Influence, with age as a significant moderator. Managerial implications include the importance of habit formation and ease of use in online health platforms to increase the usage. This study also makes a theoretical contribution by showing the relationship between UTAUT2 variables and health information seeking behavior, which has rarely been explored before. Further research with larger samples and more specific segment is recommended to enhance the generalizability of these findings.